NUTRITIONAL AND THERAPEUTIC EVALUATION OF SPIRULINA PLATENSIS - KULKARNI, SACHIN; CHAVAN, DEEPALI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present investigation was to isolate and produce Spirulina platensis on high scale for food pharmaceutical and aquaculture due to the presence of high protein content. Methods: Cultivation of Spirulina preparation of culture medium, inoculums build up, growth monitoring, harvesting, drying, procedure for protein estimation, sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and DNA isolation of Spirulina platensis. Results: The study shows that protein content of S. platensis was found to be 62% protein profile was studied through SDS-PAGE, the bands were in the range of 35 kDa–44 kDa. S. platensis contain high molecular weight DNA. The bands was seen and visualize under the transilluminator it reveals that the alga S. platensis contain high molecular weight DNA. Conclusion: The production of Spirulina by simple pH determination method suggests economic production of alga by a simple process. The DNA isolation showing that these algae contain high molecular weight DNA. However, utilization of this biomass for varied end uses, such as food, feed, aquaculture, and pharmaceuticals.